Principles of building a new ecosystem: social, economic and legal aspects - Kaipbekova S. V., Nikiforova A. A., Iusifova Z. V., Sizova A. S., Lazarev V. A., Nikulina I. E., Shchedrina E. V., Minakov A. V., Griaznykh D. V., Kruglov V. N., Gadzaova L. P., Salavatova A. M., Feoktistova L. R., Patrusheva V. A., Artemova E. E. (Principles of building a new ecosystem: social, economic and legal aspects, 2025)
social support for families raising a disabled child is one of the technologies of social work. Social support is an activity aimed at providing assistance to citizens, including parents, guardians, trustees, and other legal representatives of minor children in need of medical, psychological, pedagogical, legal, and social assistance, by engaging organizations that provide such assistance, based on interdepartmental cooperation.
Keywords: семья; содержание; социальная адаптация; social adaptation; content; family; социальная реабилитация; социальное сопровождение; комплексная реабилитация; social rehabilitation; social support; ребенок-инвалид с нарушением слуха; формы и методы социального сопровождения; disabled child with hearing impairment; forms and methods of social support; comprehensive rehabilitation